Strategi Komunikasi Politik melalui Media Sosial oleh Calon Presiden Indonesia 2024 - Adnan, Muhammad; Mona, Nailul (Politika: Jurnal Ilmu Politik, 2024)
Interactivity is among the powerful characteristic that differ social media with another kind of conventional media. Social media can facilitate any kind of communication practice, including political communication. Political communication highly needs the use of media to obtain their objectives, specifically for politician to persuade voters to choose them on election. This study aim to discover the social media strategy used by Indonesia president candidates 2024. Using internet research dan observation, Instagram feeds posts from three candidates’s account were collected and analyzed, during the start of campaign period – November 28TH  2023, until the article was written. Several aspects were assessed, including communication style, consistency, and four levels of political marketing strategy. Result shows that consistency in scheduling, writing caption, and choosing hashtag didn’t directly affect social media engagement, such as like and comment. All President Candidates manage their social media to communicate and persuade their audience or voters, but didn’t utilize the interactivity to reply the comment or build conversation via Instagram feeds. Another findings show that Instagram comment section were dominated by both fans/followers and political buzzers that interactively building conversation. Further research should be done to assess another platform and another type of political marketing content.